The translation and adaptation of kid-kiddokindlr questionnaire into Malay to measure the quality of life (qol) of school-age children with hearing impairment - Kamarul Arifin, Nur Amirah; Mohamed Zain, Nor Azrita; Wan Ahmad, Wan Aslynn Salwani (2018)
A child requires a good hearing in order to perceive auditory input at home and school. If the learning process is disturbed by hearing impairment, the quality of child’s life might be affected. Thus, the quality of life of these children should be taken into account while helping them in adapting and managing their hearing problems. In order to understand their QoL better, the English version Kid-KiddoKINDLR questionnaire is adapted and translated into Malay. The main objective of this paper is to report on the process of adapting, translating and validating the material. In addition several issues relating to these process will also be highlighted. The Malay Kid-KiddoKINDLR questionnaire is a beneficial tool particulaly to the the Malay speaking population.